2021
DOI: 10.1007/s11356-021-14463-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The effect of energy consumption on the environment in the OECD countries: economic policy uncertainty perspectives

Abstract: In this paper, we investigate the impact of energy use and economic policy uncertainties on the environment. To achieve this objective, we use the pooled mean group-autoregressive distributed lag methodology (PMG-ARDL) and Dumitrescu and Hurlin causality test on 22 Organisation for Economic Co-operation and Development (OECD) countries between 1985 and 2017. The PMG-ARDL estimation shows that energy use and economic policy uncertainties have a positive relationship with carbon dioxide emission (CO 2 ) emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 66 publications
1
25
1
Order By: Relevance
“…For the countries in our sample, the economic contraction caused by high EPU overwhelms the neglected implementation of environmental regulations, reduced commitments on environmental protection by enterprises, and the higher use of cheaper but more polluting energy sources. Although these results confirm the significant environmental impact of EPU, it is different from the empirical literature that indicates a positive longrun relationship between the two variables (Adams et al 2020;Adedoyin et al 2021a;Anser et al 2021;Atsu and Adams 2021;Danish and Khan 2020;Sohail et al 2021;Yu et al 2021;Zakari et al 2021). The difference may be due to the choice of research sample.…”
Section: Main Results and Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For the countries in our sample, the economic contraction caused by high EPU overwhelms the neglected implementation of environmental regulations, reduced commitments on environmental protection by enterprises, and the higher use of cheaper but more polluting energy sources. Although these results confirm the significant environmental impact of EPU, it is different from the empirical literature that indicates a positive longrun relationship between the two variables (Adams et al 2020;Adedoyin et al 2021a;Anser et al 2021;Atsu and Adams 2021;Danish and Khan 2020;Sohail et al 2021;Yu et al 2021;Zakari et al 2021). The difference may be due to the choice of research sample.…”
Section: Main Results and Discussioncontrasting
confidence: 99%
“…Pirgaip and Dinçergök (2020) provide evidence of unidirectional causality running from EPU to energy consumption in Japan, to CO 2 emissions in the USA and Germany, and to both energy consumption and CO 2 emissions in Canada. Zakari et al (2021) show a positive connection between EPU and CO 2 emissions in 22 OECD countries. Adedoyin et al (2021a) examine environmental issues in sub-Saharan Africa.…”
Section: Brief Literature Reviewmentioning
confidence: 87%
“…Secondly, the EPU-environment nexus' literature is investigated to draw conclusive remarks for the BRICS's economic policies. There is a wealth of literature on the relationship between EPU and CO 2 emission (Danish et al 2020a;Pirgaip and Dinçergök 2020;Yu et al 2021;Zakari et al 2021). However, there are a handful of studies using EF as a measure of environmental quality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Anser et al, (2021), [123] in higher carbon emitter countries, the policy uncertainty mitigates the pollution in the short-term while it escalades in the long run. The argument that, in the long run, policy uncertainty further deteriorates the quality of environment is also supported by the results of Zakari et al, (2021) [124], which confirmed a positive association between policy uncertainty and carbon emissions in the 22 Organisation for Economic Cooperation and Development (OECD) countries between 1985 and 2017.…”
Section: Policy Uncertaintymentioning
confidence: 72%